Potential analgesic function of the clitoris in pregnant women: A feasibility study - MM Manon Bestaux-Brethez; André Gillibert; Thibaut Sabatier; Eric Verspyck (PLoS ONE, 2025)
Currently, the clitoris is considered to exist solely for sexual pleasure. This prospective, single-centre pilot study focuses on and evaluates an alternative function of the clitoris; pain relief during pregnancy and childbirth. Conducted between 2020 and 2023 at Rouen University Hospital, France, this feasibility study challenges the assertion of the singular function of the clitoris. The primary aim was to assess the acceptability of an intervention focusing on the potential analgesic function of the clitoris. The secondary aim was to assess pain relief. Pregnant women were offered the option of self-external massage with a vibrating device (OVD) in the clitoral suspensory ligament area for pain relief. Data were collected via a self-schedule for precise use of the method, including pain assessment before and after the use of the OVD via a self-analytic visual scale. Acceptability was considered to have been achieved if the woman used the OVD at least twice. Comparisons before and after were performed by means of a student’s t-test. With respect to acceptability, among the 32 women included, 26 (81.25%) used an OVD at least twice. Despite concerns about sexual intimacy and the sensitive period of pregnancy, this preliminary feasibility study confirmed the suitability of this mechanical vibration for the majority of the women included. In terms of pain relief, these 26 women used the OVD to manage 304 painful episodes and the feeling of relief was reported in 86.2% of these episodes. Based on a small sample size, the numerical results are obviously highly relative to the disparity of situations and feelings. However, these few consistent reports of a positive analgesic effect encourage further studies into the potential analgesic function of the clitoris.